Local anesthesia as an alternative to general anesthesia in ENT surgery - a review of selected procedures - Agnieszka Parfianowicz; Alicja Surma; Arkadiusz Jaworski; Filip Grajnert; Jakub Plizga; Agnieszka Głuszczyk; Jakub Cecot; Konrad Zarzecki; Miłosz Mandryk; Nazar Holdun (Nicolaus Copernicus University in Toruń, 2024)
Surgeries and procedures in otolaryngology require close collaboration between anesthesiologists and ENT specialists, especially for operations involving the larynx and airways, which pose challenges for maintaining airway patency and visibility. Choosing the type of anesthesia, whether general or local, is crucial. This study examines the benefits and drawbacks of both types of anesthesia in tonsillectomy and adenoidectomy, tympanostomy and myringotomy, and flexible endoscopic biopsy of the pharynx and larynx. A review of current guidelines, systematic reviews  and relevant clinical cohort studies was conducted. The findings highlight several advantages of local anesthesia, including shorter operation times, reduced hospital stays, lower costs, decreased use of analgesics, and improved patient comfort.